The Influence of Training, Work Experience, and Competence on Employee Performance at Surabaya Husada Utama Hospital - Hyrnanda Era Dewanti; I Putu Artaya (NAROTAMA UNIVERSITY, Indonesia, 2019)
The purpose of this research are for known as training, work experience, and competence towards improving employee performance in Surabaya Rs Husada Utama. This research is a quantitave. The population and samples are based upon questionnaire that had been given to 56 respondesnts of Rs Husada Utama nurse in Surabaya. Data retrieval techniques by interview, observation and questionnaire. Data analysis that had been use are validity test, reability test, classic assumption test, and multiple linier analysis test. The research shows that training (x1) and work experience (x2) and competence (x3) has a significant correlation towards employee performance (Y) the value is < 0,05.